Gene manipulation in Oenococcus oeni based on a newly applicable gene gun technology - Mengrong Chen; Qiling Chen (Frontiers in Microbiology)
Oenococcus oeni is an important engineering microbe in winemaking. Detailed knowledge of its growth and metabolism in harsh wine environments could contribute to breeding elite O. oeni varieties. However, further studies on this topic do not appear to be sustained due to the lack of stable and reproducible technology to perform gene manipulation on O. oeni. Therefore, this research was designed to study gene function by exploring a newly applicable transformation technique that could perform stably and reproducibly on O. oeni. By using gene gun technology with detonation nanodiamonds as a plasmid DNA carrier, we achieved stable and reproducible plasmid DNA transformation in O. oeni. In addition, the plasmid with the chloramphenicol resistance gene allowed O. oeni SX-1b to thrive in chloramphenicol medium.